Effect of tea polyphenols on intestinal barrier and immune function in weaned lambs - Xu, Yuewen; Yin, Fuquan; Wang, Jialin; Wu, Pengxin; Qiu, Xiaoyuan; He, Xiaolin; Xiao, Yimei; Gan, Shangquan (Frontiers in Veterinary Science, 2024)
The purpose of this study was to explore the effects of tea polyphenols on growth performance, cytokine content, intestinal antioxidant status and intestinal barrier function of lambs, in order to provide reference for intestinal health of ruminants. Thirty weaned lambs (average initial weight 9.32±1.72kg) were randomly divided into five groups with six lambs in each group. The control group did not add anything but the basic diet mainly composed of Pennisetum and Corn, and the other four groups added 2, 4, 6 g/kg tea polyphenols and 50mg/kg chlortetracycline to the basic diet respectively. The experiment lasted for 42 days. As a result,dietary tea polyphenols improved the growth and stress response and reduced intestinal permeability of lambs (P < 0.05), while CTC did not affect the final lamb weight (P > 0.05). Both tea phenols and CTC significantly reduced inflammatory factors and enhanced the immune system (P < 0.05). Dietary tea polyphenols increased villus height, villus height/crypt depth , secretory immunoglobulin A (P < 0.05), and antioxidant enzymes, while decreasing MDA and apoptosis in the intestine(P < 0.05). However, compared with other groups, the content of T-AOC in jejunum did not change significantly (P > 0.05). Tea polyphenols also increased claudin-1 levels in the duodenum, jejunum, and ileum more than CTC (P < 0.05). CTC had a limited effect on the mRNA expression of Occludin and ZO-1, while tea polyphenols increased these in both the duodenum and ileum (P < 0.05). This study demonstrated that tea polyphenols can effectively improve the intestinal barrier of weaned lambs, and that they have anti-inflammatory and antioxidant effects similar to those of antibiotics. Thus, tea polyphenols could be used to replace antibiotics in ensuring safety of livestock products and in achieving the sustainable development of modern animal husbandry.